THE TAX CENTER'S ROLE IN INDIVIDUAL TAX COMPLIANCE WHEN PUTTING REGULATIONS IN PLACE HARMONIZATION OF REGULATIONS - Clara Neltje Meini Rotinsulu; Ahmad Junaidi; Nuryati Solapari (SEAN Institute, 2023)
The goal of this study is to identify and map the role of the Tax Center at the Faculty of Economics and Business at Universitas Trunojoyo Madura in fulfilling tax obligations that can increase taxpayer compliance when implementing HPP Law regulations. This study makes use of qualitative research and a case study methodology. Triangulation was used to collect data, which included interviews with four informants, observations, and document support. In-depth interviews were conducted with informants on three topics: the role of the tax center, taxpayer reactions to the HPP Law policy, and taxpayer compliance. Purposive sampling was used to select individual taxpayers, tax academics, and tax center administrators as research informants. The data analysis technique is divided into three stages: data reduction, data presentation, and conclusion drawing. The study's findings indicate that the Tax Center, as a higher education institution, plays a strategic role. One of its visions and missions aligns with the Directorate General of Taxation. The Tax Center, in addition to its educational, research, and community service functions, is actively involved in and contributes to the socialization of the most recent tax policy, namely the Law on the Harmonization of Tax Laws (HPP). The Tax Centre's existence is critical because the community, particularly universities, requires information and explanations about the Voluntary Program (PPS). One indicator of increased tax compliance in the university environment is the increased participation of taxpayers in filling out the Annual SPT even during the Covid-19.